1973
DOI: 10.1128/aem.25.5.800-806.1973
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Requirements for the Production of Enterotoxin B by Staphylococcus aureus S-6 in a Chemically Defined Medium

Abstract: A minimal chemically defined medium has been developed for growth (approximately 25 Klett units) and production of detectable enterotoxin B (approximately 5-6 ug/ml) by Staphylococcus aureus S-6. This medium contains monosodium glutamate as a source of carbon, nitrogen, and energy, three additional amino acids (arginine, cystine, and phenylalanine), six inorganic salts, and four vitamins. Increasing the concentrations of several amino acids in a series of defined media gave no increase in enterotoxin productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Since superinfection of competent cells of strain 8325-4(Xll) at high multiplicities increased the frequency of transfection (20), we also tested the effect of superinfection on the transformation. The addition of phage 11 to the transformation mixture did not increase the transformation frequency ( Table 6).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Since superinfection of competent cells of strain 8325-4(Xll) at high multiplicities increased the frequency of transfection (20), we also tested the effect of superinfection on the transformation. The addition of phage 11 to the transformation mixture did not increase the transformation frequency ( Table 6).…”
Section: Resultsmentioning
confidence: 96%
“…To be able to isolate amino acid-requiring mutants of strain 8325, we investigated the basal amino acid requirement of this strain. Several authors (1,9,11) have reported on various salt solutions for culturing S. aureus. The salt mixture reported in Table 2 supported the best growth in media containing amino acids, glucose, and vitamins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the growth profiles of strains in a medium that supports only respiratory growth. S. aureus is capable of utilizing glucose as well as glutamate as a source of carbon (47,48). Glutamate feeds directly into the TCA cycle at the ␣-ketoglutarate entry point, and we reasoned that glutamate would support respiratory growth almost exclusively.…”
Section: Figmentioning
confidence: 99%
“…Attempts have been made to determine the minimum requirements for enterotoxin production in chemically defined media , Wu & Bergdoll 1971Miller & Fung 1973). Whilst toxin production occurred in defined media containing essential salts, vitamins, and an energy source such as glucose, glutamate or amino acids, in general it was never as high as could be achieved in complex media.…”
Section: Culture Mediamentioning
confidence: 99%